The current state of legal regulation of labor relations in Ukraine - S. M. Bortnyk (Bulletin of Kharkiv National University of Internal Affairs)
The experts’ point of view regarding the concept of “labor legal relations” has been studied and the author’s definition has been given, which means the volitional, legal relationship between an employee and an employer, arising on the basis of an employment contract, regarding the employee’s performance of work with its payment and ensuring the working conditions necessary for it performance provided for by labor legislation, collective agreement and agreement of the parties.